The antibacterial properties of Malaysian tualang honey against wound and enteric microorganisms in comparison to manuka honey - Sulaiman Siti; Hassan Siti; Halim Ahmad; Gan Siew; Rahman Rosliza; Tan Hern; BS Kirnpal-Kaur (BMC, 2009)
Abstract Background Antibiotic resistance of bacteria is on the rise, thus the discovery of alternative therapeutic agents is urgently needed. Honey possesses therapeutic potential, including wound healing properties and antimicrobial activity. Although the antimicrobial activity of honey has been effectively established against an extensive spectrum of microorganisms, it differs depending on the type of honey. To date, no extensive studies of the antibacterial properties of tualang (Koompassia excelsa) honey on wound and enteric microorganisms have been conducted. The objectives of this study were to conduct such studies and to compare the antibacterial activity of tualang honey with that of manuka honey. Methods Using a broth dilution method, the antibacterial activity of tualang honey against 13 wound and enteric microorganisms was determined; manuka honey was used as the control. Different concentrations of honey [6.25-25% (w/v)] were tested against each type of microorganism. Briefly, two-fold dilutions of honey solutions were tested to determine the minimum inhibitory concentration (MIC) against each type of microorganism, followed by more assays within a narrower dilution range to obtain more precise MIC values. MICs were determined by both visual inspection and spectrophotometric assay at 620 nm. Minimum bactericidal concentration (MBC) also was determined by culturing on blood agar plates. Results By visual inspection, the MICs of tualang honey ranged from 8.75% to 25% compared to manuka honey (8.75-20%). Spectrophotometric readings of at least 95% inhibition yielded MIC values ranging between 10% and 25% for both types of honey. The lowest MBC for tualang honey was 20%, whereas that for manuka honey was 11.25% for the microorganisms tested. The lowest MIC value (8.75%) for both types of honey was against Stenotrophomonas maltophilia. Tualang honey had a lower MIC (11.25%) against Acinetobacter baumannii compared to manuka honey (12.5%). Conclusion Tualang honey exhibited variable activities against different microorganisms, but they were within the same range as those for manuka honey. This result suggests that tualang honey could potentially be used as an alternative therapeutic agent against certain microorganisms, particularly A. baumannii and S. maltophilia.